Dynamic responses of human brain and brain mimicking gels during impact - Zhou, Youjin (2017)
Recently, more attention has been paid to the head injury studies. Among these head injuries, traumatic brain injury (TBI) has been specifically explored by many researchers due to its irreversible effects and high mortality or disability. On the prevention side, the study of mechanical properties of brain tissues is essential for a better understanding of injury mechanisms. The current research aims to study the mechanical behaviour of the brain tissue under dynamic loadings by using two typical mimicking gels, and to explore the injury mechanisms and the prevention of TBI. This research program has four parts. Firstly, we conducted the compression tests and oscillatory shear tests (OSTs) to study the nonlinear and viscous behaviour of two brain mimicking gels, hydrogel and silicone gel. The compression results of the gels were compared with the experimental results of real brain tissues from literature to explore their feasibility in simulating the real brain. Time-Temperature Superposition (TTS) principle is used to obtain the master curves of storage and loss moduli in a wide range of frequency from the OSTs. An analytical method is developed to derive the compressive behaviour of the mimicking gels under different strain rates based on master curves. It is found that the two gels show nonlinear visco-elastic and significant strain rate-dependent properties and are suitable to mimic brain tissue in a range of the strain and loading rate. Secondly, impact tests were conducted to study the dynamic responses of the mimicking gels at different velocities. The non-uniform deformation of the gels was captured by a high speed camera and analysed quantitatively by two methods, marker displacement measurement and Matlab analysis methods. An interesting phenomenon was observed that the gels compressed alternately at the two ends during the impact and the raised lateral ring propagated like a wave at the lower velocity impact (2 m/s), but it disappeared at higher velocity impacts (6 and 20 m/s). Further investigation of the compression force demonstrates that compression velocity had a significant effect on the force-strain behaviour of the gels. Thirdly, an analytical study is conducted on spherical wave propagation within soft materials. Based on the analytical model, a numerical study is conducted for the influence of the loading shape of particle velocity and mechanical parameters on the responses of the brain tissue. The analysis reveals that the loading shape of the particle velocity and bulk modulus have significant influences on the peak value and the attenuation of stress and strain, while viscosity shows little effect on them. Finally, a detailed finite element (FE) head model is developed to simulate the scenario of front-rear head impact in football games. The brain injury risk is assessed based on the mechanical responses of the two heads and the risk curves. The effectiveness of headgear made of energy absorption foams is investigated in protecting players’ head. The simulation reveals that it is easy for bare head to get injured in two-head impact when the impact velocity v≥2.5 m/s and the proposed headgear can provide effective protection for the head at the impact velocity within 4 m/s.